Indolenine – dibenzotetraaza [14] annulene Ni (II) complexes as sensitizers for dye - sensitized solar cells - Ramle, Abdul Qaiyum; Khaledi, Hamid; Hashim, Ameerul Hazeeq; Mingsukang, Muhammad Ammar; Arof, Abdul Kariem; Ali, Hapipah Mohd; Basirun, Wan Jefrey (Elsevier, 2019)
A new series of macrocyclic Ni (II) complexes having indolenine and dibenzotetraaza [14] annulene (DBTAA) moieties were synthesized and tested for their application as sensitizers in dye - sensitized solar cells (DSSCs). The structures are furnished with anchoring groups of ethyl ester (8a, 8b, and 8c) or carboxylic acid (9c) on the indolenine moiety and hexyloxy (8b) or neopentyloxy (8c, 9c) groups on the DBTAA moiety. The best performance was exhibited by dye 9c, which under constant AM 1.5G solar simulation (100 mW cm −2 ) using I − /I 3 − electrolyte gave a short-circuit current J sc = 0.43 mA cm −2 , an open-circuit voltage V oc = 0.41 V and a fill factor FF = 0.528, corresponding to an overall conversion efficiency of η = 0.093%. This is the first investigation of macrocyclic DBTAA derivatives as sensitizers for DSSCs applications. © 2019 Elsevier Ltd